The Effect of the Implementation of ICOFR on the Quality of SKPD Financial Statements: An Empirical Study on the Local Government of Bengkalis Regency - Putri Ramadani; Fachroh Fiddin (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of the implementation of Internal Control over Financial Reporting (ICoFR) on the quality of financial reports of the Regional Apparatus Work Unit (SKPD) in the Bengkalis Regency Government. ICoFR is an internal control system that focuses on the reliability of financial reporting, based on five COSO components, namely the control environment, risk assessment, control activities, information and communication, and monitoring. This study uses a quantitative approach by distributing questionnaires to SKPD officials who are directly involved in the process of preparing financial statements. Data was processed using multiple linear regression analysis through SPSS software to test the effect of ICoFR application on the quality of financial statements measured through the dimensions of relevance, reliability, comprehension, and comparability. The results of the study are expected to show that the implementation of ICoFR effectively has a positive and significant effect on improving the quality of SKPD's financial statements. These findings are a strategic reference for local governments in strengthening the internal control system and realizing accountable and transparent financial governance.